DISEÑO DE PRODUCTO AGROTURÍSTICO PARA LA PARROQUIA MALACATOS, CANTÓN LOJA. - FIGUEROA JUMBO, MARÍA JOSÉ (2024)
The concept of agrotourism refers to an activity associated with the rural environment, the agricultural and agrarian environment, that is, it is an alternative tourism that is characterized by activities organized by farmers as part of the development of their primary activity, to which tourists are invited, resulting in economic compensation for the services provided. The following research is entitled "Agrotourism Product Design for the Parish of Malacatos, Canton Loja", which aims to create an agrotourism route for the Malacatos parish. As part of the research work, the following specific objectives had to be established: diagnose the agro-tourism potential of Malacatos parish; The second objective was to design an agro- tourism route that would allow Malacatos parish to develop its agro-tourism capacity. For the development of the following research the methodology of Marvin Blanco called design and operation of agrotourism products was applied. The methodology used in this study included bibliographic, descriptive, analytical, and deductive methods, and for the collection of data, survey, interview, direct observation, and SWOT analysis were used. According to the results of the research, the design of a route called "agrotourism and handicrafts route Malacatos" was developed, which incorporated the most important and representative agricultural farms of the parish; as part of the proposed itinerary, the option of a two-day tourist package has been introduced. This route was established with the purpose of promoting economic development in the sector. In conclusion, it can be mentioned that within the parish there are several agricultural farms. According to the information gathered, eleven farms were established, of which six were selected. As part of the selection process, several factors were considered, including the infrastructure of the farms, the scenic and cultural potential of the farms, as well as the predisposition of the farms. Therefore, new tourism alternatives can be generated in which tourists will be able to observe, learn, and experience the varied tasks and activities performed by these producers, thereby generating agrotourism as well as developing strategies for the development of the place.